Galicia: "The land of the Meigas" - Martinez, Beatriz (E- Revista de Estudos Interculturais, 2023)
This research delves into the cultural phenomenon of Meigas, or witches, in the region of Galicia, Spain, and their economic impacts on the local community. The Meigas has a rich and storied history in Galicia, with roots in ancient Celtic and pagan traditions. In modern times, they have transformed, going from being viewed as taboo to being embraced and commercialized as a symbol of the region. They play a significant role in the region's place branding strategy, attracting tourists and promoting the unique cultural heritage of Galicia through the development of popular tourist attractions and related merchandise. This research will examine the history of the Meigas in Galicia, including the evolution of their connotation over time. It will also explore the economic impacts of the Meigas on the local community, including their role as a place brand for Galicia and their contribution to the regional economy. Through a comprehensive analysis of the history and contemporary significance of Meigas in Galician society, this research aims to provide a nuanced and in-depth understanding of this fascinating cultural phenomenon.